2023
DOI: 10.1002/aisy.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Bistable, Pneumatically Actuated Microgripper Fabricated Using Two‐Photon Polymerization and Oxygen Plasma Etching

Abstract: Fabrication of actuatable micromechanisms onto the tip of submillimeter medical instruments permits microsurgery, cellular‐level intervention, targeted drug delivery, or placement of microimplants. In these systems, a common lack of integrated microsensors or optical feedback prohibits stabilizing closed‐loop control. Moreover, the low stiffness of compact actuator and microfabrication limitations lead to difficult control. Herein, a compact bistable open‐loop micromechanism mounted on a small (170 μm) capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…8f). 216 For applications that rely on the capacity to deliver fluids via esDLW-printed components, Acevedo et al presented an approach for DLW-printing microfluidic structures with arbitrary geometries directly onto 360 μm-in-diameter fused silica tubes (Fig. 8g).…”
Section: Dlw Of Microfluidic Entities Directly Atop Meso/ Microscale ...mentioning
confidence: 99%
See 1 more Smart Citation
“…8f). 216 For applications that rely on the capacity to deliver fluids via esDLW-printed components, Acevedo et al presented an approach for DLW-printing microfluidic structures with arbitrary geometries directly onto 360 μm-in-diameter fused silica tubes (Fig. 8g).…”
Section: Dlw Of Microfluidic Entities Directly Atop Meso/ Microscale ...mentioning
confidence: 99%
“…217 Key drawbacks of the these approaches, however, stem from the need for custom-built capillary holders to support loading into the DLW 3D printer. [215][216][217] Not only must each individual capillary be loaded into the holder manually (i.e., by hand), but in cases with high numbers of capillaries, it can be difficult to maintain consistent surface heights and axial orientations for each capillary. As a result, the alignment protocols required for each individual capillary-which are typically performed manually (i.e., by hand/eye under brightfield microscopy)prior to initiation of the DLW printing process can be exceedingly time and labour intensive.…”
Section: Dlw Of Microfluidic Entities Directly Atop Meso/ Microscale ...mentioning
confidence: 99%
“…Power et al expanded this system in 2023 toward grippers which showed bistable behavior (see Figure 6C). [163] By oxygen plasma etching, the authors achieved 400 nm thin substructures in their chevron-style bistable gripper design able to undergo structural changes toward pressure changes. Alsharhan et al combined printed pneumatically actuated grippers with printed transistor structures.…”
Section: D Printed Microfluidic Devicesmentioning
confidence: 99%
“…Adapted with permission. [ 163 ] Copyright 2023, The Authors. D) SEM image of a spinneret which was printed inside of a microfluidic channel structure.…”
Section: Microfluidicsmentioning
confidence: 99%
“…To the best of our knowledge, the first example of a 3D nanoprinted magnetically actuated optomechanical device was recently demonstrated by Rothermel et al, 11 where ferromagnetic fluids were capillary-filled into integrated microchannels to achieve translational and rotational displacement of a micro-optical component using an external magnetic field. Also, Power et al 12 introduced a 3D nanoprinted bistable microgripper with pneumatic actuation that operates without continuous power consumption or closed-loop control.…”
Section: Introductionmentioning
confidence: 99%